2013
DOI: 10.1007/s11356-013-1865-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light, microbial activity, and sediment resuspension on the phosphorus immobilization capability of drinking water treatment residuals in lake sediment

Abstract: Drinking water treatment residuals (WTRs), nonhazardous by-products generated in a drinking water treatment plant, can be reused to immobilize phosphorus (P) to control the internal P loading from lake sediments for eutrophication control. Reasonably, before practical application, it is essential to determine the P immobilization capability of WTRs in lake sediments under various conditions. In this work, laboratory scale experiments were conducted to investigate the effects of light, microbial activity, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…termed P-capping agents; Meis et al, 2012Meis et al, , 2013Spears et al, 2013a;Wang et al, 2013aWang et al, , 2013b, etc. Among these methods, in situ P immobilization technology, which involves adding the Pcapping agents into sediments to increase the P binding capacity of the sediments or placement of a layer of the P-capping agents at the sediment-water interface to create a barrier between the sediment and the overlying water, have gained a great deal of attention by many researchers and is considered as a promising method for controlling the internal loading of P in lakes (Gibbs et al, 2011;Márquez-Pacheco et al, 2013;Meis et al, 2012Meis et al, , 2013Reitzel et al, 2013;Spears et al, 2013aSpears et al, , 2013bvan Oosterhout and Lürling, 2013;Wang and Pei, 2013;Wang et al, 2012;Wang et al, 2013a;Wang et al, 2013b;Wang et al, 2013c;Wang et al, 2013d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…termed P-capping agents; Meis et al, 2012Meis et al, , 2013Spears et al, 2013a;Wang et al, 2013aWang et al, , 2013b, etc. Among these methods, in situ P immobilization technology, which involves adding the Pcapping agents into sediments to increase the P binding capacity of the sediments or placement of a layer of the P-capping agents at the sediment-water interface to create a barrier between the sediment and the overlying water, have gained a great deal of attention by many researchers and is considered as a promising method for controlling the internal loading of P in lakes (Gibbs et al, 2011;Márquez-Pacheco et al, 2013;Meis et al, 2012Meis et al, , 2013Reitzel et al, 2013;Spears et al, 2013aSpears et al, , 2013bvan Oosterhout and Lürling, 2013;Wang and Pei, 2013;Wang et al, 2012;Wang et al, 2013a;Wang et al, 2013b;Wang et al, 2013c;Wang et al, 2013d).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of some P-capping agents such as the lanthanum-modified bentonite clay (Phoslock ® ) and the aluminum/ferrum based drinking water treatment residuals (Al/Fe based WTRs) to control the internal loading of P from sediments into the water column have been investigated (Gibbs et al, 2011;Márquez-Pacheco et al, 2013;Meis et al, 2012Meis et al, , 2013Reitzel et al, 2013;Spears et al, 2013aSpears et al, , 2013bvan Oosterhout and Lürling, 2013;Wang and Pei, 2013;Wang et al, 2012;Wang et al, 2013a;Wang et al, 2013b;Wang et al, 2013c;Wang et al, 2013d). However, these P-capping agents are suffered from some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated effective P sorption by WTRs and the high stability of WTRs-sorbed P under a variety of environmental conditions (Makris et al 2004;Agyin-Birikorang and O'Connor 2007;Oliver et al 2011;Wang et al 2012a). Due to the high P adsorption capacity of WTRs, the productive reuse of WTRs to control P pollution in water, soils, and sediments has been examined, including WTR use as a soil amendment to reduce P loss from soils (Agyin-Birikorang et al 2009;Silvetti et al 2014), use as media within a constructed wetland to remove excessive P from wastewater (Hu et al 2014), and use as a stabilizer to control P release from sediments (Wang and Pei 2013;Wang et al 2014). There is also potential for WTRs use as a sorbent for metals and metalloids.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Pei 2013; Netten et al 2014). Atmospheric reoxygenation, microbial growth and metabolism is also negatively affected by large plant density(Mowjood and Kasubuchi 2002).…”
mentioning
confidence: 99%